Can surf culture foster loyalty towards surf destinations? - Reis, Patrícia (2022)
The sport of surfing is gaining increasing importance in the context of tourism. Surf tourism has emerged as one promising product of certain regions worldwide. Surfing, as a sport and as a lifestyle, has been grounded in surf culture, which is recognized as a potential attraction factor for certain surf destinations. Although previous research has been undertaken in the field of surf tourism, the impact that the visitors’ perceptions of a destination’s surf culture have on the overall destination image and on loyalty towards that destination is not represented in the peer-reviewed literature. Therefore, a research model is proposed and tested, aiming to contribute to the advancement of knowledge regarding the relevance and influence of surf culture. A survey questionnaire was carried out among visitors to a surf destination in Portugal – Peniche (N = 430). The model was tested using partial least squares structural equation modelling (PLS-SEM). Results reveal that the perceptions of surf culture contribute to a better overall destination image and a higher loyalty towards the destination, with the overall image also having a positive impact on loyalty. However, different components of surf culture have distinct impacts on overall image and loyalty. The study provides important theoretical contributions in terms of surf culture and the components of a surf destination image, as well as offers useful insights for the development of effective management strategies for surf tourism destinations.